“Reclaiming Our Schools”: Interviews with Black Lives Matter at School Organizers Tamara Anderson and Jesse Hagopian - Stark, Lauren Ware (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
This piece weaves together excerpts from interviews with two key leaders of the Black Lives Matter at School movement, which were conducted as part of a broader ethnographic study of educator movements. In their respective interviews, Anderson and Hagopian discuss their roles in the Black Lives Matter at School movement, suggesting some of the ways that this movement has grown from 2016 to 2020.